Pengaruh Perceived Usefulness, Social Influence dan Perceived Risk terhadap Intention To Use Qris - Cheery Sheffia Agustine; Ketut Sunaryanto (GEMILANG: Jurnal Manajemen dan Akuntansi, 2026)
The development of digital technology has driven the birth of various digital financial innovations, particularly QRIS, which plays a crucial role in accelerating economic growth and digital financial transformation. This study aims to evaluate the influence of Perceived Usefulness, Social Influence, and Perceived Risk on Intention to Use QRIS in Greater Jakarta (Jabodetabek). The research method used is multiple linear regression using SPSS software. The method used in this study is a quantitative method. The population in this study were QRIS users in the Greater Jakarta area. Therefore, to meet the required sample, this study began with a pre-test distributing questionnaires using Google Forms to 30 respondents, resulting in a sample of 170 respondents. The findings in this study prove that Perceived Usefulness influences Intention to Use QRIS. Interestingly, Perceived Risk was also found to influence Intention to Use QRIS. Meanwhile, Social Influence has no influence on Intention to Use QRIS. The findings in this study contribute to QRIS service providers in increasing perceived benefits and managing risks clearly to expand adoption rates.